Disconnected Pancreatic Duct in Children With Walled OFF Necrosis: Impact on Outcomes of Endoscopic Drainage. Issue 1 (July 2019) - Nabi, Zaheer; Basha, Jahangeer; Lakhtakia, Sundeep; Shava, Upender; Pal, Partha; Ramchandani, Mohan; Gupta, Rajesh; Kalapala, Rakesh; Darisetty, Santosh; Tandan, Manu; Reddy, Duvuur Nageshwar
ABSTRACT: Objectives: Disconnected pancreatic duct syndrome (DPDS) is frequently encountered in cases with walled off necrosis (WON). The impact of DPDS on the outcomes of pancreatic fluid collections (PFCs) is not well known. In this study, we aim to evaluate the incidence of DPDS and its clinical impact on the outcomes of endoscopic ultrasound (EUS)-guided drainage of PFC in children. Methods: All children with symptomatic WON who underwent EUS-guided drainage using metal stents were included in the study. At 4 weeks, pancreatic ductal anatomy was evaluated, and metal stents removed. All the children were followed at regular intervals and evaluated for the recurrence of PFC and the development of new-onset diabetes. Results: A total of 32 children (28 boys, median age 15 years) underwent EUS-guided drainage of WON. Resolution of WON was documented in all children at 4 weeks. Pancreatic ductal anatomy using magnetic resonance retrograde cholangiopancreatography and endoscopic retrograde pancreatography was available in 30 (93.7%) children. Of these, DPDS was documented in 25 (83.3%) children including proximal disconnection in 12 and distal disconnection in 13 children. Recurrent PFC and new-onset diabetes were found in 5 (20%) and 2 (8%) children with DPDS, respectively. Of the 5 recurrences of PFC, endoscopic reintervention was required in 3 children. Conclusions: Majority of the children with DPDS do not develop a symptomatic recurrence of PFC after the removal of cystogastric stents. DPDS may be a risk factor for the development of new-onset diabetes. However, future prospective studies are needed.